Batch-injection stripping voltammetry (tube-less flow-injection analysis) of trace metals with on-line sample pretreatment - Trojanowicz, Marek (2005)
The most essential limitation of batch-injection analysis (BIA) methodology compared to other flow methods (CFA, FIA, SIA) is the lack of possibility of on-line sample processing in the measuring system. Some procedures of on-line sample pretreatment in BIA are possible by changing the plastic tip of the automatic micropipette used for sample injection into a flow-through reactor, e.g. by packing it with a bed of a solid sorbent. This concept is employed in the voltammetric stripping determinations of trace metals using a bed of commercial chelating resin Chelex-100. It was found that, besides the electrochemical preconcentration of analytes in the form of amalgams on the surface of mercury thin film electrodes, an approximately 10-fold additional preconcentration can be achieved on the packed sorbent bed by using different volumes of aspirated sample solution and eluent. This procedure allows also efficient elimination of some matrix effects.